Social Media, Advertising, and Disinformation: A Transdisciplinary Analysis on Fake News and Its Advertising Use in Digital Consumer Culture - García López, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In the digital age, social media has reshaped advertising and the flow of information, facilitating the spread of disinformation through strategies like microtargeting and programmatic advertising. The interplay between algorithms and sensationalist content contributes to social polarization and undermines trust in institutions. This paper examines the relationship between social media, advertising, and disinformation from an interdisciplinary perspective, employing critical discourse analysis of advertising campaigns that rely on fake news and clickbaits. Additionally, it explores regulatory proposals and media literacy initiatives to mitigate these phenomena and reconsider current advertising models.